Cone-complementary manifold method for stability and failure analysis of jointed/fractured rock masses. (March 2021) - Fan, Huo; Huang, Duruo; Wang, Gang
Abstract: Taking advantage of a unique dual-cover system, the numerical manifold method (NMM) is a powerful tool for analyzing stability and progressive failure of jointed/fractured rock masses. In this study, a new implicit cone complementary (CC) formulation is integrated into the NMM to capture the dynamic frictional-cohesive contact problems in jointed/fractured rock masses. The innovative numerical method, termed as the CC-NMM, circumvents numerical difficulties of using artificial contact penalty and open-close iteration in the original NMM. Benchmark examples demonstrate that both mechanical energy and translational momentum of the system are conserved in the proposed CC-NMM. Several examples are further designed to illustrate the excellent performance of the CC-NMM in simulating the progressive failure pattern and stability of the jointed/fractured rock masses.